AB1117 24 Hour Crystal Microscopy Improves Diagnosis in Cases of CPPD. (9th June 2015) - Reilly, E.; Wilcox, J.; Maggs, T.; Mackay, K.
Abstract : Background: Acute monoarthritis presents a diagnostic challenge on call and generates many inpatient Rheumatology referrals. Patients may undergo unnecessary intravenous antibiotics or arthroscopy for fear of missing septic arthritis. Calcium pyrophosphate deposition disease (CPPD) is the most challenging crystal arthropathy to prove on synovial fluid analysis, due to the relative fragility of crystals and lack of persistent at microscopy. We present an example of service change which altered diagnostic rates for crystal arthropathies, and would streamline care. Objectives: To assess the effect of widened access to crystal microscopy in the management of acute monoarthritis in a district general hospital. Methods: Regional histopathology and local microbiology databases were reviewed for synovial aspirates between January 2013 and June 2014. This spanned a change from histopathology to microbiology as primary laboratory for analysis in December 2013. Microbiology were trained in crystal microscopy, and the service was extended from 9am-5pm to 24 hour. Results were cross-referenced with Cyberlab biochemical result system for further details. Timings of lab samples were recorded. Results: 180 synovial fluid samples were received during January to December 2013, and 155 during December 2013 to June 2014 in our hospital. Graph 1 shows the change in results across the service change. Most notably the rates of CPPD rose substantially and amorphous crystalline debris fell. A&E admission rates also fell. All samples pre intervention were analysed within working hours. 24 hour microscopy service saw 59% of samples analysed out of hours (5pm-9am or weekends). Wait times for sample analysis fell from 46 hours to 11.8 with the change in service. Conclusions: Service development has led to demonstrable changes in diagnoses (increased rates CPPD, reduced amorphous crystalline debris, but maintained rates of MSU and negative results). Accurate early diagnosis reduces admissions and would reduce patient exposure to unnecessary procedures. References: Zhang et al. European League Against Rheumatism recommendations for calcium pyrophosphate deposition. Part I: terminology and diagnosis. Ann Rheum Dis 2011 Apr;70(4):563-70. doi: 10.1136/ard.2010.139105. Epub 2011 Jan 7. Tausche et al. A 3-day delay in synovial fluid crystal identification did not hinder the reliable detection of monosodium urate and calcium pyrophosphate crystals. J Clin Rheumatol 2013 Aug;19(5):241-5. doi: 10.1097/RHU.0b013e31829cde53. Acknowledgements: Many thanks to the laboratory staff at Torbay Hospital. Disclosure of Interest: None declared